Metagenomic Insights Into the Microbial Community and Nutrient Cycling in the Western Subarctic Pacific Ocean - Li, Yingdong; Jing, Hongmei; Xia, Xiaomin; Cheung, Shunyan; Suzuki, Koji; Liu, Hongbin (Frontiers in Microbiology, 2018)
The composition and metabolic functions of prokaryotic communities in the western subarctic Pacific (WSP), where strong mixing of waters from the Sea of Okhotsk Sea with the the East Kamchatka Current transfers it to Oyashio Current, were investigated using a shotgun metagenome sequencing approach. Functional genes belonging to metabolisms related to nutrient cycling (nitrogen, sulfur, carbohydrate, iron and amino acid) were differently distributed between the surface and deep waters of the WSP. Genes related to nitrogen metabolism were mainly found in deep waters, where Thaumarchaeaota, Sphingomonadales and Pseudomonadales were closely associated and performing important role in ammonia oxidation, assimilatory nitrate reduction and dissimilatory nitrate reduction processes, respectively. In addition, orders affiliated to Spingobacteriia and Alphaproteobacteria were crucial for sulfate reduction and abundant at 3000 m, whereas orders affiliated to Gammaproteobacteria, which harbored the most sulfate reduction genes, were abundant at 1000 m. Additionally, in the Oyashio Current, the prokaryotes were more likely to consume energy for synthesizing cellular components. Also, genes encoding iron transport and siderophore biosynthesis proteins were in low abundance, indicating that the iron was not a limiting factor in it. In contrast, in the East Kamchatka Current, prokaryotes were more likely to directly utilize the amino acids and absorb iron from the environment. Overall, our data indicated that the transformation from the East Kamchatka Current to the Oyashio Current reshapes not only the composition of microbial community, but also the function of the metabolic processes. These results extended our knowledge of the microbial composition and potential metabolism in the WSP.